Biomass and population structure of Constrictotermes cyphergaster (Silvestri) (Isoptera: termitidae) in the dry forest of caatinga, northeastern Brazil - Vasconcellos,Alexandre (2007)
Biomass and population structure of Constrictotermes cyphergaster (Silvestri) were studied in an area of dry forest of caatinga in the State of Paraiba, northeastern Brazil. Twelve nests of different sizes were randomly collected, being six during the dry season (November 2004 and 2005) and six during the wet season (March 2004). Soldier and worker populations varied between 4880 and 118800 individuals per nest. The ratio between soldiers and workers did not significantly vary between seasons. Biomass (measured as fresh weight) of individuals varied between 13.9 and 408.8 g per nest, and soldiers and workers had significantly greater biomass during the wet season. The estimated density of nests of C. cyphergaster was 59.0 ± 22.53 active nests/ha. Quantitative data of the study colonies and data on the nest abundance showed that C. cyphergaster encompassed some 278.2 individuals/m², with approximately 0.9 g (fresh weight)/m². These data suggest that C. cyphergaster is an important consumer of vegetal matter and, therefore, an important species affecting the nutrient cycling and energy flow in the caatinga vegetation.